Developement of Karonda (Carisa Carandus .L) Based Products - Sheeja Majeed K (Department of Home Science, College of Agriculture, 1995)
The present experiment entitled “Development of karonda based products” was aimed at developing products for the utilization of the underexploited karonda. In this study organoleptic, nutritional, shelf life qualities and also consumer acceptance and preference of the developed products were investigated.